Morocco : First Review Under the Arrangement Under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Morocco's First Review Under the Arrangement Under the Precautionary and Liquidity Line (PLL). The Moroccan authorities are committed to sustaining sound policies. The government's economic program remains in line with key reforms agreed under the PLL arrangement, including to further reduce fiscal and external vulnerabilities, while strengthening the foundations for higher and more inclusive growth. The transition to greater exchange rate flexibility initiated in 2018 is expected to enhance the economy's capacity to absorb shocks and preserve its external competitiveness. The current favorable economic environment remains supportive to continue this reform in a carefully sequenced and well-communicated manner. The report recommends that continued reforms are needed to raise potential growth and reduce high unemployment levels, especially among the youth, increase female labor participation, and reduce regional disparities. Reforms of education, governance, the labor market, and the business environment would help support more private sector-led growth and job creation.